Peningkatan Aktivitas Dan Hasil Belajar Fiqih Pada Materi Sujud Syukur Melalui Penerapan Model Time Token Siswa Kelas VIII-1 MTsN 8 Aceh Besar Tahun Pelajaran 2018/2019 - Nurdiana, Nurdiana (Yayasan Darul Hasanah Aceh, 2023)
The purpose of this research is to increase the activity and learning outcomes of Fiqh on the subject of the enjoyment of prayer and the beauty of life for students VIII-1 MTsN 8 Aceh Besar in the 2018/2019 academic year. the model used in this classroom action research is the time token learning model. The subjects of this classroom action research were class VIII-1 students of MTsN 8 Aceh Besar in the 2018/2019 academic year. The number of students is 36 students with a total of 6 male students and 26 female students. This classroom action research was carried out in the 2018/2019 academic year. This classroom action research was carried out over a period of 3 months, from September 2018 to November 2018 in odd semesters. Each cycle consists of planning, implementing, observing and reflecting. The research procedure consisted of pre-research, cycle one planning, cycle one action implementation, cycle one observation, cycle one reflection, cycle two planning, cycle two action implementation, cycle two observation and cycle two reflection. The data collection technique is to collect test scores which are carried out at the end of each lesson in each cycle using the question instrument (written test). Observation data is done by looking at the activeness of students in the learning process. Data were analyzed by means of percentage statistics. The results showed that the activity and student learning outcomes in the pre-cycle, namely 59.38% increased to 71.88% in cycle I and in cycle II increased to 87.50%. Student learning activities have increased from the moderate category to good and the good category has increased to very good.